(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In the work, the authors consider the labor market as a certain economic environment, where, in conditions of competition and with the help of supply and demand mechanisms, the employment indicator and the level of wages are formed. The article analyzes the factors affecting supply and demand. The concept of wages in the labor market is revealed. Explains how wages are generated in different markets. The reasons for the differentiation of the rates of wages of workers are revealed. On the basis of the developed regulations, employers will be able to regulate the level of wages, focusing on the labor market, and workers will be able to conclude that their wages depend on qualifications and desire to develop, using a system of advanced training and a training system.